Hubungan Preeklamsia dengan Kejadian Berat Bayi Lahir Rendah di Klinik Fatiha - Nabila, Nabila Aswina; Harahap, Dewi Anggriani; Afiah (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Data from the World Health Organization (WHO) shows that in 2019 as many as 45% of under-five deaths occurred in the first month of life and almost one million neonatal deaths occurred on the day of birth. Low birth weight is a condition when a baby is born with a body weight of less than 2500 grams. The aim of this research is to determine the relationship between preeclampsia and the incidence of low birth weight babies at the Fatiha Clinic in 2022. This research design uses quantitative research methods with a case control approach. Case samples were taken using total sampling technique and control samples using simple random sampling. The research was carried out at the Fatiha Clinic. The research population of all newborns at the Fatiha Clinic was 174 newborns. There were 35 babies born who experienced Low Birth Weight and 139 babies who did not experience Low Birth Weight. The research uses a secondary data checklist sheet. Univariate and Bivariate data analysis using the Chi-Squere test. These results indicate a relationship between preeclampsia and the incidence of low birth weight babies, with a p value of 0.001 < 0.05. For this reason, the clinic frequently provides health education to the public regarding the importance of paying attention to parity factors in planning pregnancy.